The rate of recovery in renal function when patients with HIV infection discontinue treatment with tenofovir. Issue 8 (18th March 2014) - Young, J; Wang, Q; Fux, CA; Bernasconi, E; Furrer, H; Vernazza, P; Calmy, A; Cavassini, M; Weber, R; Battegay, M; Bucher, HC; Swiss HIV Cohort Study
<x xml:space="preserve">Abstract</x> Objectives Tenofovir is associated with reduced renal function. It is not clear whether patients can be expected to fully recover their renal function if tenofovir is discontinued. Methods We calculated the estimated glomerular filtration rate (eGFR) for patients in the Swiss HIV Cohort Study remaining on tenofovir for at least 1 year after starting a first antiretroviral therapy regimen with tenofovir and either efavirenz or the ritonavir‐boosted protease inhibitor lopinavir, atazanavir or darunavir. We estimated the difference in eGFR slope between those who discontinued tenofovir after 1 year and those who remained on tenofovir. Results A total of 1049 patients on tenofovir for at least 1 year were then followed for a median of 26 months, during which time 259 patients (25%) discontinued tenofovir. After 1 year on tenofovir, the difference in eGFR between those starting with efavirenz and those starting with lopinavir, atazanavir and darunavir was – 0.7 [95% confidence interval (CI) −2.3 to 0.8], −1.4 (95% CI −3.2 to 0.3) and 0.0 (95% CI −1.7 to 1.7) mL/min/1.73 m2, respectively. The estimated linear rate of decline in eGFR on tenofovir was −1.1 (95% CI −1.5 to −0.8) mL/min/1.73 m2 per year and its recovery after discontinuing tenofovir was 2.1 (95% CI 1.3 to 2.9) mL/min/1.73 m2 per year. Patients starting tenofovir with either lopinavir or atazanavir appeared to have the same rates of decline and recovery as those starting tenofovir with efavirenz. Conclusions If patients discontinue tenofovir, clinicians can expect renal function to recover more rapidly than it declined.